SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN KARYAWANMENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Seprindo Adi Putra; Suraya -; Erna Kumalasari Nurnawati (Jurnal SCRIPT, 2018)
Management of human resources (HR) of a company affect many aspects of the determinants of the success of the company's work. One of the most important in the management of human resources in a company is the selection of employee recruitment to spur employee morale in improving dedication and performance, but in PT.Bimasakti Multi Synergy company current selection method of employee acceptance still use manual calculations, so needed Decision Support System (DSS) in optimizing employee recruitment selection. DSS for employee recruitment aims to provide information, guide, provide predictions and directing information to the personnel in order to make better decisions. To support the accuracy of the data on the DSS for employee recruitment processed by a system then required a method that can serve as an automatic selection of each data criteria are diverse, the method chosen is Simple Additive Weighting (SAW). SAW method is appropriate for the decision-making process because it can determine the weight value for each attribute, then proceed with a ranking process that will select the best aternatif from some of the best alternatives. The result of the DSS for employee recruitment can assist the personnel department of PT.Bimasakti Multi Sinergy Company to recommend applicants to the management section. This is because the results of the assessment are granted eligibility status such as RECOMMENDED or NOT RECOMMENDED. The results can then be displayed based on the largest or smallest value, making it easier for the personnel to choose the best alternative from a number of available alternatives.